PENGARUH STRUKTUR MODAL, KEPUTUSAN INVESTASI DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA SEKTOR PERUSAHAAN PROPERTY AND REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Reza, Nadia; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to examine and analyze the influence of modalities, investmentdecisions and dividend policy on corporate value. Where the variable used in this study iscapital, and the number of dependent variable is the value of the company. The sampleused is secondary data derived from the financial statements of property and real estatecompanies listed on the Indonesia Stock Exchange (IDX) period 2011 to 2015. This studyuses secondary data from the company's financial statements. Samples and sampling usingpurposive sampling technique. Data analysis using multiple linear regression analysis, ttest, F test, and test of coefficient of determination. Data analysis using multiple linearregression analysis with SPSS 20. The results of this study indicate that the variables ofcapital structure and investment decisions (t test) on corporate influence, while the policyvariables do not affect the value of property companies and real estate mentioned in theIndonesia Stock Exchange. The simultaneous test results (f) there is no influence ofstatistical variables, investment returns and dividend policy on firm value on property andreal estate companies mentioned in Indonesia Stock Exchange.Keywords: Capital Structure, Investment Decision, Dividend Policy, and Value Company